HISTORICAL DEVELOPMENT OF FAMILY STUDIES AS A DISTINCT ACADEMIC DISCIPLINE (Годишен зборник на Филозофски факултет - Скопје, 2025)
This paper aims to explore the evolution of Family Studies as a distinct academicdiscipline, focusing on its interdisciplinary nature, the theoretical challenges it faces,and its institutional development in the United States. Unlike classical scientific disciplineswith a unified paradigm and clear theoretical roots, family studies have emergedas a result of a dialogue among multiple scholarly fields—Sociology, Psychology, Anthropology,History, Demography, Gender Studies, and other related disciplines. Thisinterdisciplinary distinctiveness, while enriching the analytical dimension of the field,simultaneously leads to methodological fragmentation and the absence of a coherenttheoretical framework. The paper analyzes both sides of this debate—the critiques oftheoretical dependence and the support for interdisciplinary innovation—as key to understandingthe disciplinary status of Family Studies.This paper is based on a historical-analytical method, through which key institutions,academic publications, and milestones in the field’s development are mapped,with particular attention to the societal and academic factors that have influenced itsinstitutionalization. Special emphasis is placed on the analysis of the American context,its process of institutionalization, and its development across different phases. Additionally,the most significant research centers and academic journals that have contributedto establishing family studies as a legitimate scientific field are examined. Inthis way, the paper offers a systematic overview of the consolidation process of FamilyStudies as a distinct discipline, assessing its scientific relevance and potential for furtherdevelopment.